UPAYA MENINGKATKAN KINERJA PEGAWAI MELALUI KEPUASAN KERJA DAN KOMITMEN ORGANISASI: (Studi Pada Biro Umum Sekretariat Daerah Provinsi Banten) - Kurnia, Noerma; Hidayatullah, Ade Syarief; Lutfi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Organizations need to create a harmonious atmosphere at work, make employeesfeel valued in their work, provide employees with satisfaction with informationcirculating and other relationships in the organization. The problem in this researchis formulated how to carry out effective internal communication in order to improveemployee performance at the Banten Provincial Secretariat General Bureau whichis supported by strengthening job satisfaction and organizational commitment. Thepopulation in this study were employees at the General Bureau of the BantenProvincial Secretariat, amounting to 220 people consisting of 50 ASN and 170 NonASN employees with a total sample of 95 people through stratified randomsampling. Collecting data using a questionnaire which was analyzed by the SEMPLS method. The results of the study prove that internal communication has asignificant effect on organizational commitment, job satisfaction and employeeperformance. This study also proves that there is a significant effect of jobsatisfaction and organizational commitment on employee performance.